PAULUS SANG ENTREPRENEUR - Junior Natan Silalahi (VISIO DEI: JURNAL TEOLOGI KRISTEN, 2019)
This article examines Paul's independence as a Gospel Preacher who lives as an entrepreneur. The Apostle Paul, an apostle for Gentiles, has particular expertise in making tents - used as a support for funding - to help continue the preaching of the gospel. He does not want to burden the congregation he serves by funding the preaching of the gospel. His expertise is used as much as possible to sustain it in service. As an apostle, he is not ashamed to be forthright about what he is doing as a tent maker. And its primary purpose is the expertise to make tents used as a bridge for preaching the gospel. Thus there are at least two essential things obtained from this topic: first, the independence of funds as an evangelist, and second, expertise as a bridge of evangelism. The method of research conducted is qualitative. The study carries out a theological approach through biblical studies. In this research, the author will describe Paul as an entrepreneur and an entrepreneur of evangelistic bridges. The findings in this study showed that gospel preachers must emulate Paul, who made his expertise a pillar of service so that it did not burden the congregation served. The church must learn to accept the fact that there are pastors who live as entrepreneurs.